PENGARUH SIKAP PERAWAT TERHADAP PERILAKU PEMILAHAN SAMPAH RUMAH SAKIT DIRUANG GICU RSUP Dr.HASAN SADIKIN BANDUNG - Anita Putri Wijayanti; Emylia Fiskasari; Yusuf Efendi (POLITEKNIK PIKSI GANESHA, 2019)
This study aims to determine the effect of nurses' attitude towards sorting out hospital rubbish in the GICU room of RSUP Dr. Hasan Sadikin Bandung.The research method used by the writer is quantitative with descriptive approach. Data collection by observation in the field, questionnaires, and literature study. The sample in this study amounted to 41 people, using saturated sampling.The results showed that there was a significant and positive influence between nurses' attitudes towards waste sorting behavior at RSUP Dr. Hasan Sadikin Bandung seen from the statistical test results obtained p value> X2 table that is 5.105> 3.841 and t count> t table which is 14.821> 2.023). The research results obtained an R number of 0.922. This shows that there is a very strong link between nurses' attitudes toward waste sorting behavior. Obtained a figure (R Square) of 0.849 or 84.9%. This shows that the percentage contribution of the influence of the independent variable (nurses' attitudes) to the dependent variable (waste sorting behavior) was 84.9%.From the research found the following problems: 1) Nurses dispose of waste not in accordance with the type of waste (for example non-medical waste disposed of in medical bins), 2) Recycling waste such as infused plabots that are not exposed to body fluids or blood of patients disposed of in medical waste, whereas recycled waste has to dispose in a special garbage bin.Thus, the advice given to improve the problems are: 1) Supervising nurses to dispose of rubbish in a place that has been provided and in accordance with the type of rubbish, 2) Providing counseling about the impact of improper hospital waste sorting and 3) Remind nurses to obey the SOP for separating hospital waste.